FTA utilization of Philippine imports - Francis Mark A. Quimba; Maureen Ane D. Rosellon; Sylwyn C. Calizo (Philippine Institute for Development Studies (PIDS), 2020)
Free Trade Agreements (FTAs) are known to enhance trade through reduction or elimination of barriers, such as tariffs on imported goods. The difference between the preferential tariff rate under an FTA and the most-favored-nation (MFN) rate can be significant enough to encourage trade under an FTA. The Philippines has signed several FTAs and has enjoyed a reduction and even the elimination of tariffs on specific commodities. This research aims to understand the relationship between preferential margin and FTA utilization rates in the case of the Philippines. It uses an empirical model to estimate this relationship using an FTA import ratio as a variable for utilization and the difference between MFN and FTA tariff rates as a variable for margin. Findings suggest that the preferential margin is positively associated with the utilization rates for FTA agreements. Results are found to be relatively robust after controlling for different fixed effects variables. Among the Philippines' FTA partners, margin is revealed to be significant in increasing imports from its ASEAN neighbors. Furthermore, the study found a positive and significant relationship between margin and imports of nearly all commodity groups.
Keywords: 330; FTA utilization; Philippines; imports; FTA utilization rate; preferential margin; margin of preference